Analysis and Design of an Integrated Magnetics Planar Transformer for High Power Density LLC Resonant Converter - Chul-Wan Park (IEEE, 2021)
Recent studies on compact and lightweight electronic devices have demonstrated that the LLC resonant converter (LRC) can facilitate achieving high efficiency and high power density. Moreover, employing a planar transformer can further improve the overall system power density. Although the planar transformer can assist in reducing the size of the converter, its high magnetic coupling makes the leakage inductance too small for a resonant inductor in the LRC. Therefore, an extra inductor must be employed separately, leading a considerable decrease in the power density. From this reason, significant research on integrated magnetics has been conducted to combine a transformer and external inductor into a single core. However, they require additional wires or magnetic sheets, and their structures are complex and costly. To overcome these limitations, the integrated magnetics planar transformer (IMPT) for a high power density LRC is proposed in this paper. In the proposed approach, since the primary wire is split into each side leg of the EE-type magnetic core and each operates as a transformer and a resonant inductor alternatively, an external inductor or additional wires are unnecessary. In addition, since the magnetic flux density of the IMPT is approximately equivalent to that of conventional transformer, the core size and the number of turns are almost the same. Therefore, the proposed IMPT features higher efficiency and power density without additional size and costs. To confirm the validity of the proposed IMPT, the operational principles, theoretical analysis, design considerations, and experimental results from a 350 W prototype are presented.